2010
DOI: 10.1021/es102213f
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Mussel Gene Expression Profile Induced by Okadaic Acid Exposure

Abstract: Seasonal seawater temperature increases define optimal growth conditions for Dinoflagellate species which can reach high concentrations in water column and also in filter-feeding organisms like Mytilus galloprovincialis. Commonly produced by Dinophysis and Prorocentrum spp., okadaic acid (OA) and its analogues are responsible for the Diarrheic Shellfish Poisoning (DSP) syndrome in humans. Closure of shellfishing grounds is therefore recommended by the EU when DSP toxin levels in shellfish exceed 16 μg OA 100 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
52
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 39 publications
11
52
2
Order By: Relevance
“…In the current study, the expression of ubiquitin-conjugating enzyme E2 and SINA-like protein were all up-regulated in mussel after exposure to P. lima, suggesting that P. lima and associated DSP toxins induced ubiquitination/proteasome activity, which might give a possible explanation of the degeneration of the digestive cells after OA exposure in previous reports (Auriemma and Battistella, 2004;Wang et al, 2012). Consistent with our observation, using cDNA microarray, Manfrin et al (2010) found a series of mRNAs involved in proteasome activity were overexpressed such as a partial mRNA for ubiquitin C-variant with an ubiquitin-domain and a polyubiquitin in the digestive gland of mussels after OA exposure.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the current study, the expression of ubiquitin-conjugating enzyme E2 and SINA-like protein were all up-regulated in mussel after exposure to P. lima, suggesting that P. lima and associated DSP toxins induced ubiquitination/proteasome activity, which might give a possible explanation of the degeneration of the digestive cells after OA exposure in previous reports (Auriemma and Battistella, 2004;Wang et al, 2012). Consistent with our observation, using cDNA microarray, Manfrin et al (2010) found a series of mRNAs involved in proteasome activity were overexpressed such as a partial mRNA for ubiquitin C-variant with an ubiquitin-domain and a polyubiquitin in the digestive gland of mussels after OA exposure.…”
Section: Discussionsupporting
confidence: 92%
“…Actually, OA-induced changes in cytoskeletal architecture and cellecell contact have been extensively reported (Leira et al, 2001;Espiña and Rubiolo, 2008;Vale and Botana, 2008;Vilariño et al, 2008;Espiña et al, 2010;Wang et al, 2011;Hanana et al, 2012;Huang et al, 2013;Opsahl et al, 2013). Using a mussel cDNA microarray, Manfrin et al (2010) found that 9% of up-regulated transcripts in mussel induced by OA exposure were potentially involved in cytoskeleton organization. Hanana et al (2012) observed that the exposure of clam heart to OA at 1 mM for 24 h could induce disorganization of the actin cytoskeleton, rounding and detachment of the fibroblastic cells.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Currently, a mussel cDNA digestive gland microarray fed for five weeks with OA contaminated nutrient reported a general up-regulation of transcripts coding for stress proteins and those involved in cellular synthesis [33]. The Pacific oyster C. gigas is a suspension-feeding bivalve mollusk, of great interest as a study model given its ecological, economic, public health, and genomic relevance because it has a completely sequenced genome [34], [35].…”
Section: Introductionmentioning
confidence: 99%
“…Also gene-centered studies take advantage of the massive production of ESTs which currently contributes to the identification of molecules and pathways underlying the mussel response to various natural and experimental conditions [45][48]. Among the 67,726 ESTs and 4680 aminoacid sequences publicly available for the Mytilus genus, about 29 and 32%, respectively, refer to M. galloprovincialis (www.ncbi.nlm.nih.gov, June 2011).…”
Section: Introductionmentioning
confidence: 99%